New stratigraphic data of the Oligo-Miocene transgressive cover of the Ghomaride units (Northern Internal Rif, Morocco): Implications on tectonosedimentary evolution - Hlila, Rachid; Chalouan, Ahmed; El Kadiri, Khalil; Sanz de Galdeano, Carlos; Martín Pérez, José Antonio; Serrano, Francisco; López-Garrido, A. C.; Maaté, A.; Guerra-Merchán, Antonio (Sociedad Geológica de España, 2008)
13 páginas, 4 figuras, 2 tablas. [EN] New biostratigraphic and field data are gathered from the two Oligo-Miocene marine transgressive cover of the Rifian Ghomaride units: i) the latest Oligocene-Aquitanian Fnidek-Ciudad Granada cycle, the top of which is here dated with planktonic foraminifera as latest Aquitanian and ii) the Burdigalian Sidi Abdeslam-Viñuela cycle, for which five outcrops are newly discovered north of the city of Tetuan. These outcrops display pelitic sequences containing siliceous horizons in their upper levels. These levels yielded nannofossil assemblages indicating the middle Burdigalian Sphenolithus belemnos zone. Regionally, both cycles may occur in the same principal depocentres, but undergo significant lateral and vertical change in their stacking pattern. Indeed, while in the central parts of the depocentres the two successive cycles may conformably stack in a near stratigraphic continuity, in the marginal parts an erosional and/or a low-angle angular unconformity may separate them. Far from the main depocentres, the Fnidek and Sidi Abdeslam cycles independently rest on the Paleozoic basement through basal conglomerates, suggesting displacement of the areas of sedimentation in the change of cycle. These tectonically mediated paleogeographic changes culminated with gravitational back-slide processes that resulted in the emplacement of Jbel Zem Zem Numidian massif over the middle Burdigalian marine levels topping the Sidi Abdeslam-Viñuela cycle. This emplacement was initiated by a docking-induced back-thrusting, and subsequently triggered by a post-collision extensional event. A possible Tertiary tectonic scenario for the western front of the Alboran domain is proposed herein. [ES] Se aportan nuevos datos bioestratigráficos y de campo de la cobertera oligo-miocena de las unidades gomárides (Zona Interna Rifeña) concernientes: i) al ciclo Oligoceno terminal- Aquitaniense de las formaciones Fnidek-Ciudad Granada, cuya parte superior se ha datado en este trabajo con foraminíferos ...